Patient’s Perspective Regarding the Elective Surgical Procedure during Covid19 pandemic - Badkur, Mayank; Puranik, Ashok; Sharma, Naveen; Baskaran, Suruthi; Prakash, Satya; Lodha, Mahendra (Archives of Clinical and Biomedical Research, 2021)
Context: The ongoing Covid-19 pandemic and the subsequent nationwide lockdown, has impacted all aspects of society including the medical profession. In hospitals, the focus has mainly shifted to prevention and treatment of Covid-19 infection. Owing to this, all elective surgeries are being postponed and only emergent surgeries are being performed. This has affected the patients differently depending on the progression of disease and development of complications. Aim: The aim of this study is to evaluate the attitude of the patients regarding their planned surgical treatment in view of COVID 19 pandemic. Settings and Design: Hospital based; Cross-sectional; Telephonic survey Methods and Material: A well-structured telephonic scripted questionnaire was administered to all patients who were given an appointment for any elective surgery. Data was collected regarding the status of disease including complications and the patient’s perspective on the method of treatment. Patients who developed complications or underwent emergency surgery or surgery elsewhere were excluded. Statistical analysis used: Collected data was entered in MS Office Excel spreadsheet and analysis was done using SPSS software. Results: The man to women ratio was 2.3:1. The mean age of patients was 41.16 years. A total of 86 patients were included in the study. Almost all (98.8%) were aware that the lockdown and withholding of elective surgeries were directed to prevent the spread of coronavirus infection. Among 34 patients with progressive disease, 88.2% were willing to undergo the surgical procedure and 73.5% were willing to visit hospital within a week or two. Among 46 patients, who were Willing to continue the treatment on wait and watch policy, 45.7% patients wanted to wait for more than 2 months for their treatment, and 93.5% patients were avoiding hospital visit b